The Influence of Work Culture, Environment, and Motivation on the Academic Staff Performance in Universitas Negeri Semarang - Siti Mursidah; Moh Khoiruddin; Lidiadni Septantri (Universitas Negeri Semarang, 2023)
This study aims to determine the influence of the work environment, culture, and motivation on the work performance of Universitas Negeri Semarang (UNNES) academic staff. This study used work culture (X1), work environment (X2), and work motivation (X3) as independent variables; and their correlation to the academic staff’s work performance as dependent variables (Y). A total of 138 respondents were involved and chosen using a random sampling technique from 691 academic staff working as lecturers and educational supporting staff. The data was collected using self-assessment questionnaires, and then collected data were tabulated, reduced to avoid bias, and labeled for independent analysis. The analysis process was run using descriptive and quantitative approaches. The results showed that work culture significantly affects academic staff’s working performance. Because positive work culture influences the work environment that triggers high performance; however, this study found that motivation has no significance toward work performance. This research found that work achievement and their perspective against reward or additional income (remuneration) mostly influence motivation. Further study needs more variables, including work satisfaction, leadership, personal background, and other variables that may contribute to working performance, are recommended for the next study